The Imaging and Cognition Genetics Conference 2011, ICG 2011: A Meeting of Minds - Le Hellard, Stephanie; Hanson, Isabel (Frontiers in Neuroscience, 2012)
In June 2011, seventy researchers from the disciplines of cognitive science, genetics, psychology, psychiatry, neurobiology and computer science gathered in Os, Norway, for the first Imaging and Cognition Genetics meeting. The aim of the conference was to discuss progress, enhance collaboration and maximise resource sharing within this new field. Here we summarise some of the major themes that emerged from ICG 2011.